Menedzseri "forradalom" és innovációs kényszer: kitörési pontok a Kádár-korszak mezőgazdaságában - Schlett, András (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The aim of the essay is to demonstrate the characteristics of industrial like productive systems gaining ground in the Hungarian agriculture from the beginning of the sixties. In course of this the article concentrates upon the emphasis and analysis of those factors which determined the offset and development of the new production organising form in special way. It presents what role industrialising played in the evolution, successes and failures of the given development models, and what agent role it played in the enterprise system established in the sixties and seventies and in the organization of different integra-tion forms. In the end the history of industry like agriculture - as an outbreak attempt - can partly give an answer to the deeper correspondences of the operational problems of the socialist economic system.